A practical approach of managing knowledge in organization - Wan Maseri Wan Daud (Penerbit Universiti Malaysia Pahang, 2011)
This book is aimed to propose a balanced and integrated approach of how a implement knowledge management within an organization by effectively taking advantage of practical tools and techniques.